Role of CTLA4 in the proliferation and survival of chronic lymphocytic leukemia. - Amit K Mittal (Public Library of Science (PLoS), 2013)
Earlier, we reported that CTLA4 expression is inversely correlated with CD38 expression in chronic lymphocytic leukemia (CLL) cells. However, the specific role of CTLA4 in CLL pathogenesis remains unknown. Therefore, to elucidate the possible role of CTLA4 in CLL pathogenesis, CTLA4 was down-regulated in primary CLL cells. We then evaluated proliferation/survival in these cells using MTT, (3)H-thymidine uptake and Annexin-V apoptosis assays. We also measured expression levels of downstream molecules involved in B-cell proliferation/survival signaling including STAT1, NFATC2, c-Fos, c-Myc, and Bcl-2 using microarray, PCR, western blotting analyses, and a stromal cell culture system. CLL cells with CTLA4 down-regulation demonstrated a significant increase in proliferation and survival along with an increased expression of STAT1, STAT1 phosphorylation, NFATC2, c-Fos phosphorylation, c-Myc, Ki-67 and Bcl-2 molecules. In addition, compared to controls, the CTLA4-downregulated CLL cells showed a decreased frequency of apoptosis, which also correlated with increased expression of Bcl-2. Interestingly, CLL cells from lymph node and CLL cells co-cultured on stroma expressed lower levels of CTLA4 and higher levels of c-Fos, c-Myc, and Bcl-2 compared to CLL control cells. These results indicate that microenvironment-controlled-CTLA4 expression mediates proliferation/survival of CLL cells by regulating the expression/activation of STAT1, NFATC2, c-Fos, c-Myc, and/or Bcl-2.